Conceptualising Lobola as a perpetuator of gender-based violence in South Africa through Intsika - Montle, Malesela Edward (Penerbit Universiti Kebangsaan Malaysia, 2020)
South Africa, in the present day, is overwhelmed by a vexing toll of domestic violence and femicide. News reports in the country confirm that some women are murdered and abused by their intimate partners if not spouses. This worsens the dilemma when husbands become perpetrators instead of protectors of their wives as anticipated by the society by virtue of their identities as husbands. This study singles out the cultural practice of Lobola as one of the impetus of abuse against women and aims to explore its role in the perpetuation of gender-based violence. The malicious act of domestic violence besieging married women threatens the future of South Africa and the success of women. As a result of the nature of this abuse, women tend to lose self-esteem, suffer from depression and ultimately die. Therefore, this qualitative study which is guided by a narrative analysis design sought to conceptualise the rapport between the element of marriage, Lobola and gender-based violence in South Africa. It is underpinned by the theory of feminism and has thrived on the narrative analysis of the South African telenovela, Intsika which epitomises gender-based violence incited by Lobola. This abuse against women might conventionalise the so-called ‘men are trash’ idea, foster marital phobia and marriage decline in South African. This noted, Lobola needs to be redefined in such a way that it leaves no misconception about wives being properties of their husbands. The study has predicated on the South African context using the Xhosa couple in the selected telenovela where it found that Lobola is often excused to marginalise women within matrimonial affairs, thus, endless reports emerge about deaths and horrific abuse of women in South Africa.